The Challenge of Museum Brand Enhancement with Social Media in Yogyakarta Indonesia - Ayu Helena Cornellia (Media Wisata, 2020)
Museum as heritage tourism has its own unique selling point. The success of the museum in some western countries has triggered museum development in developing countries including Indonesia. However, the number of visitors to the museum in Yogyakarta (Central Java) is not as high as other popular tourist attractions in the city. The previous study found some reasons underlying this condition which are lack of promotion, lack of infrastructure facilities and lack of human resources quality. This paper is aimed to find out the challenge of museum brand enhancement with the use of social media as it has a great role in promotion. Social Media strategy is investigated in MuseumSonobudoyo, Museum Pendidikan Indonesia UNY and Museum Gumuk PasirYogyakarta with a qualitative descriptive approach. The result of the study found that the use of social media in the museum is not maximum because there is no person in charge of social media development, limited supporting tools and lack of political support